Analysing climatic variability and extremes events in the Himalayan regions focusing on mountainous urban agglomerations. Issue 26 (13th December 2022) - Diksha,; Kumar, Amit; Lal, Preet
Abstract: The present study highlights the long-term variations in temperature and precipitation using time series datasets of CRU and ERA5-Land across the Himalayan region. The Mann-Kendall and Sen's slope-based trend analysis exhibited an apparent warming trend in the region, with higher increase in Tmin (1.5 °C) and comparatively lower increase in Tmax (0.8 °C) during 1901–2018. The joint CCl/WCRP/JCOMM based 19 extreme indices elucidated an increasing frequency of warm days (16%) in Central Himalayan urban agglomerations (HUAs) with a declining number of cold days (−6%) and cold nights (−4%) during 2000–2019. The moderate decline in the wet days (8%) and consecutive wet days (−5 days/20 years) observed in all HUAs compared to an increasing frequency of the consecutive dry days (3 days/20 years). Study reported higher warming in Kathmandu UA, while increased precipitation in Srinagar UA, and contributes to framing climate change adaptation and mitigation strategies in the mountainous system.